Readmission Trends Related to Unruptured Intracranial Aneurysm Treatment - Mehta, Tapan; Desai, Ninad; Patel, Smit; Male, Shailesh; Khan, Adam; Grande, Andrew Walker; Tummala, Ramachandra Prasad; Jagadeesan, Bharathi Dasan (Frontiers in Neurology, 2021)
BACKGROUND AND PURPOSE Given the high mortality rate following aneurysmal SAH, prophylactic treatment of unruptured intracranial aneurysms (UIA) is considered for selected patients thought to be at high risk for aneurysmal rupture. Hospital readmission rates can serve as a surrogate marker for the safety and cost-effectiveness of treatment options for UIAs; we present an analysis of the 30-day rehospitalization rates and predictors of readmission following UIA treatment with surgical and endovascular approaches. METHODS We retrospectively analyzed data from the National Readmission Database (NRD) derived from the Healthcare Cost and Utilization Project for the year 2014. The cohort included patients with a primary discharge diagnosis of a treated unruptured aneurysm. The primary outcome variable was the 30-day readmission rate in open surgical vs. endovascularly treated groups. The secondary outcomes included predictors of readmissions, and causes of 30-day readmissions in these two groups. RESULTS The 30-day readmission rate for the surgical group was 8.37% compared to 4.87% for the endovascular group. The index hospitalization duration was longer in the surgical group. A larger proportion of the patients readmitted following surgical treatment were hypertensive (76.35%, versus 63.43%), but the prevalence of other medical comorbidities was comparable in the two treatment groups. CONCLUSIONS There is a higher likelihood for 30-day readmission, longer duration of initial hospitalization and a lower likelihood of discharge home following surgical treatment of UIAs when compared to endovascular treatment. These findings, however, do not demonstrate long-term superiority of one specific treatment modality.